Airworthiness : an introduction to aircraft certification - De Florio, Filippo (Butterworth-Heinemann, 2011)
Airworthiness: An Introduction to Aircraft Certification and Operations, Third Edition, once again proves to be a valuable, user-friendly reference guide for certification engineers engaged in professional training and practical work in regulatory agencies and aircraft engineering companies. The discussions reflect the recent changes in the EASA-FAA regulations and also include the concepts of flight safety and airworthiness; the ICAO and civil aviation authorities; airworthiness requirements; type certifications and the type-certification process; production of products, parts, and appliances; certifications of airworthiness; and rules for spaceworthiness. Since publication of the second edition, airworthiness regulation and certification around the world have gone through significant changes. For example, EASA structure has completely changed, FAA rules are no longer applicable, substantial changes have been made in the international airworthiness regulations and certification procedures, and unmanned aircraft have evolved technically and operationally. The changes in airworthiness regulations in the last five years have been striking, changing the way in which we look at airworthiness and certification processes around the world.